Development of mathematical models of synthesis of the O-antigens atoxigenic strains of Vibrio cholerae based on the model of the synthesis of O-antigen secreted in the process of culturing the virulent strain of vibrio сholerae M-41 Ogawa in the production of cholera vaccine - A. V. Komissarov; O. A. Volokh; Yu. A. Aleshina; A. K. Nikiforov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
The paper contains the results of the development of mathematical models for O-antigen synthesis by atoxigenic cholera vibrio strains KM 262 biovar El Tor serovar Ogawa, KM 263 biovar El Tor serovar Inaba, and M 377 O139 serogroup based on the modeling of the synthesis of O-antigen, produced in the course of cultivation of the virulent Vibrio cholerae M 41 strain belonging to classical biovar, serovar Ogawa. The data obtained provide the possibility to successfully perform the task of up-scaling the designed pilot technology for cultivation of atoxigenic cholera vibrio strains to be utilized on commercial-scale bioreactors.